Estimation of the forces acting on the tibiofemoral joint during knee extension exercises - Rodrigo Rico Bini; Felipe Pivetta Carpes; Joelly Mahnic de Toledo; Jefferson Fagundes Loss (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n1p35 The objectives of this study were to: (1) evaluate the resistive torque of an open kinetic chain strength-training machine for performing knee extensions, and (2) perform an analysis estimating internal forces in the tibiofemoral joint. During a fi rst phase of the study, measurements were taken of the machine under analysis (external forces), and then calculations were performed to estimate forces on the lower limb (internal forces). Equations were defi ned to calculate human force (HF), and the moment of muscular force (MMF). Perpendicular muscular force (MFp) and joint force (JFp), axial muscular force (MF") and joint force (JF"), and total muscular force (MF) and joint force (JF) were all calculated. Five knee angles were analyzed (zero, 30, 45, 60, and 90 degrees). A reduction was observed in HF at higher knee angles, while MF and JF also increased at the same time. HF was always lower than the load selected on the machine, which indicates a reduced overload imposed by the machine. The reduction observed in MFp and JFp at higher knee angles indicates a lower tendency to shear the tibia in relation to the femur. At the same time, there was an increase in JF" due to higher MF". The biomechanical model proposed in this study has shown itself adequate for the day-to-day needs of professionals who supervise orient strength training.